Implications of Industry Dynamics on Strategy, Case: LoRa Tracking System in Reindeer Husbandry in Finland - Konttaniemi, Heikki; Suopela, Trifon; Vatanen, Matti (Lapin ammattikorkeakoulu, 2019)
The purpose of this study was to examine business forces underlying the animal tracking industry in Finland. The goal was to find key factors that affect the competition in the industry. The results were meant to be used as a guide to develop business wise a competitive technology solution to track reindeer. Key results from the study indicate that the animal tracking industry in Finland is rather small with 4 main players ruling the market. Products are very a like, supplier components are standardized, buyer groups are only few, substitute products are expensive lacking features and new entrants can possess a credible threat to enter the market. Lora-based Rural IoT death indicator prototype is an example of potential new entrant that can discover strategic sweet spots to enter the market. The study provides unique perspective to animal tracking industry in Finland and the results can be used as a starting point when strategically planning new products, services or business models to the proposed market. The study was funded by the Regional Council of Lapland and produced by the TEQU research group.